2006
DOI: 10.2139/ssrn.2316964
|View full text |Cite
|
Sign up to set email alerts
|

Age, Women, and Hiring: An Experimental Study

Abstract: of the MIT public finance and labor lunches, the NASI annual conference, and the Boston College Center for Aging and Work seminar for insightful comments. Any errors are my own. AbstractAs the baby boom cohort reaches retirement age, demographic pressures on public programs such as Social Security may cause policy makers to cut benefits and encourage employment at later ages. This prospect raises the question of how much employer demand exists for older workers. This paper reports on a labor market experiment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
168
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(185 citation statements)
references
References 30 publications
15
168
0
2
Order By: Relevance
“…Oreopoulos (2011) considers more occupations, but restricts his attention to jobs that required three to seven years of experience and an undergraduate degree, and to applications that possess those qualifications. Lahey (2008) sends resumes only to entry-level jobs, defined as jobs requiring no more than one year of education plus experience.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Oreopoulos (2011) considers more occupations, but restricts his attention to jobs that required three to seven years of experience and an undergraduate degree, and to applications that possess those qualifications. Lahey (2008) sends resumes only to entry-level jobs, defined as jobs requiring no more than one year of education plus experience.…”
Section: Discussionmentioning
confidence: 99%
“…Similar patterns have been observed for callbacks in U.S. correspondence studies. For example,Lahey (2008) found that younger women were 40 percent more likely to receive callbacks than older women Neumark, Burn and Button (2015). find considerably more age discrimination in hiring against older women than older men in a large resume correspondence study.14 The key conditions are that roughly the same number of ads are targeted at men versus women in the sample as a whole, and that the distribution of men's and women's unobserved relative values across jobs is symmetric.…”
mentioning
confidence: 99%
“…They found robust evidence of age discrimination against older women; however, interestingly, they found much weaker and less robust evidence against older men . Other field experiments (Farber et al , 2016, 2017, 2019; Lahey, 2008a) also found evidence of age discrimination against older women, although these studies did not test for gender differences as their sample was restricted to women . In Table 2, I show means of weeks unemployed between 1962 and 1967 by gender and age using the Annual Social and Economic Supplement (ASEC) of the Current Population Survey (CPS) (also known as the ‘March CPS’) .…”
Section: Introductionmentioning
confidence: 93%
“… In studying age discrimination, Lahey (2008a) restricted the sample to women because time out of labor force is less likely to signal negative unobservable productivity. For Farber et al (2016, 2017, 2019), their main objective was to study the impact of unemployment duration on call back rate.…”
mentioning
confidence: 99%
“…For the OECD 11 , these tend to have a negative perception of these workers due to their difficulty in adapting to technological and organisational changes, labour costs, which increase more with age than does productivity, and for the difficulties many companies may face in adjusting the work conditions to labour legislation. Lahey 12 and Neumarket al 13 found evidence of workforce discrimination against older women in the United States, which makes it more difficult for them to find a new job if they lose theirs or wish to change.…”
mentioning
confidence: 99%